The effectiveness of self-compassion based training program on resilience of mothers of children with type 1 diabetes in Isfahan, Iran - Marzieh Najafi; Mousa Alavi; Mohammad Akbari; Sima Gezelbash (Wolters Kluwer Medknow Publications, 2022)
Background: Concerns about the complications of diabetes and the responsibility of constantly managing a child's blood glucose are stressful for parents, especially for mothers, and can reduce their resilience. This study aimed to investigate the effectiveness of a self-compassion-based training program on the resilience of mothers of children with type 1 diabetes. Materials and Methods: This is a randomized clinical trial study. The statistical population of the study consisted of all mothers of children with type 1 diabetes who were being treated at the Isfahan Endocrine and Metabolism Research Centre, Iran. The study samples were recruited conveniently, 64 of whom were randomly divided into two groups (compassion training program = 32; control group = 32). The intervention group participated in eight training sessions. Data were analyzed using t-test, and Analysis of Covariance (ANCOVA) tests for between-group comparisons of dependent variables. Results: There was no significant difference between the mean scores of resilience before intervention (p > 0.05). Mean scores of resilience in the intervention group were significantly higher than the control group immediately (F1,60 = 9.726 p = 0.003) and 1 month after intervention (F1, 60 = 13.146, p = 0.001). Conclusions: It may be worthwhile to suggest compassion-based training program for mothers of children with type 1 diabetes to improve their resilience.